Ulam stabilities for a class of nonlinear mixed fractional integro--differential equations (Nonlinear Studies, 2020)
The aim of this study is to investigate stabilities of Ulam- Hyers, Ulam-Hyers-Rassias and semi-Ulam-Hyers-Rassias on closed interval [a,b] for a class of nonlinear mixed fractional integro-differential equation involving psi -Hilfer fractional derivative. Banach  fixed point theorem is used to obtain our main results.